Effect of tranexamic acid dissolved in warm, cold, and room-temperature irrigation fluid on complications during and after TURP surgery: a double-blind, randomized clinical trial - Masoomeh Salehi; Behzad Imani; Shirdel Zandi; Hamed Haghiabi; Somayeh Souri (African Journal of Urology)
Abstract Background Transurethral resection of the prostate (TURP) surgery, as a common surgical technique for cases of benign prostatic hyperplasia, can often lead to various complications during and after the procedure. Among these, intraoperative bleeding and postoperative shivering are highly prevalent. Accordingly, the present study aimed to compare three combinations of tranexamic acid (TXA) dissolved in warm, cold, and room-temperature irrigation fluids to determine their greater effectiveness in reducing bleeding and postoperative complications, such as shivering, following TURP. Methods This prospective, double-blind clinical trial was conducted from April to November 2023 at Imam Khomeini Hospital in Alashtar, Iran. 100 patients scheduled for TURP were selected via convenience sampling and randomly assigned into four groups using a four-block and permutation design. The groups were as follows: Intervention Group A (TXA dissolved in cold irrigation fluid), Intervention Group B (TXA dissolved in room-temperature irrigation fluid), Intervention Group C (TXA dissolved in warm irrigation fluid), and the Control Group (room-temperature irrigation without TXA). Intraoperative bleeding was measured using a photometer, hemoglobin levels were assessed with the Cell-Dyn3200 hematology analyzer, and postoperative shivering was evaluated using the Crossley and Mahajan scale. Results Postoperative bleeding was significantly lower in Intervention Group A compared to the other groups (P < 0.05). Hemoglobin levels decreased significantly over time (P < 0.05), but no significant inter-group differences in hemoglobin changes were observed (P > 0.05). Postoperative shivering was lowest in Intervention Group C and highest in Intervention Group A (P < 0.05). Conclusions Combining TXA in a cold irrigation fluid potentially reduces intraoperative bleeding, but is associated with a higher incidence of postoperative shivering than the other groups.